Anion gap and base deficit are predictors of mortality in acute pesticide poisoning. (February 2019) - Lee, SB; Kim, DH; Kim, T; Lee, SH; Jeong, JH; Kim, SC; Park, YJ; Lim, D; Kang, C
Background: Acute pesticide poisoning has long been a serious problem as a method of suicide worldwide. This poisoning is a highly fatal condition that requires a rapid and precise diagnosis for adequate treatment. However, various studies on mortality predictor factors have been insufficient for whole pesticide treatments. We hypothesized that the initial plasma anion gap (AG) and base deficit (BD) are reliable prognostic factors. Methods: A retrospective study analyzed 561 patients with a diagnosis of acute pesticide poisoning between January 1, 2014 and June 30, 2017. The initial AG and BD values were divided into quartiles according to the number of patients. Survival at 30 days from admission was estimated using the Kaplan–Meier survival analysis. Receiver-operator characteristic (ROC) curves were drawn, and the areas under the curve for AG and BD for mortality were calculated. Results: Fifty-eight (10.3%) of 561 patients died within 30 days. The highest AG quartile (>22 mEq/L) was associated with an increased risk of 30-day hospital mortality. Compared to patients with an AG less than 14.7 mEq/L, these patients had a 4.18-fold higher risk of 30-day hospital mortality and the highest BD quartile (>7.9 mEq/L) was associated with an increased risk of 30-day hospital mortality. Compared to patients with a BD less than 1.4 mEq/L, these patients had 2.23-fold higher risk of 30-day hospital mortality. The areas under the ROC for AG and BD curve were 0.699 and 0.744, respectively. Conclusions: Initial high AG and BD values could predict mortality and require precise intensive care.